Heart Plasticity in Response to Pressure- and Volume-Overload: A Review of Findings in Compensated and Decompensated Phenotypes - Pitoulis, Fotios G.; Terracciano, Cesare M. (Frontiers in Physiology, 2020)
The adult human heart has an exceptional ability to alter its phenotype to adapt to changes in environmental demand. This response involves metabolic, mechanical, electrical, and structural alterations, and is known as cardiac plasticity. Understanding the drivers of cardiac plasticity is essential for development of therapeutic agents. This is particularly important in contemporary cardiology, which uses treatments with peripheral effects (e.g., on kidneys, adrenal glands). This review focuses on the effects of different hemodynamic loads on myocardial phenotype. We examine mechanical scenarios of pressure- and volume overload, from the initial insult, to compensated, and ultimately decompensated stage. We discuss how different hemodynamic conditions occur and are underlined by distinct phenotypic and molecular changes. We complete the review by exploring how current basic cardiac research should leverage available cardiac models to study mechanical load in its different presentations.